Activity Pattern of School/University Tenants and their Family Members in Metro Manila – Philippines - Kecorius, Simonas (Archīum Ateneo, 2018)
Existing studies that focus on personal exposure to or the deposition dose of particulate pollution in developing regions are limited. Hence, in this study, as a first step, we present results on how people spend their daily time in Metro Manila, Philippines. This information is critical to assessing personal exposure to and the deposition dose of particulate pollutants. We found that people spend less time at home on workdays than weekends (52% versus 70%), the fraction of time spent at work/school increases with age until retirement, adult males spend less time at home than females (18% versus 28%), and people spend most of their time indoors (84%). The biggest difference from previous studies is the discovery that people in Metro Manila spend 11% of their daily time on average in transit traffic, which is up to 2.2 times more than in Europe, America, Korea, or China. Longer times in transit traffic subject the population of Metro Manila to a higher risk of increased exposure to toxic pollutants and adverse health symptoms. The main results of this research will be used in an upcoming study on the personal deposition dose of soot.